2015
DOI: 10.1007/s40071-015-0099-5
|View full text |Cite
|
Sign up to set email alerts
|

Bloom of the two dinoflagellates Ceratium furca and Diplopsalis lenticula in a mangrove estuary of Thailand

Abstract: Knowledge of the planktonic species that appear in mangrove estuaries in tropical areas is still poor. We believe that case report data on the appearance of species is important for clarifying the ecosystem of the mangrove estuary. We report in this paper on the occurrence of blooms and discuss the factors that influence blooming, based on an observed bloom consisting of two dinoflagellates in the mangrove estuary of Samut Songkhram, Thailand, in December 2012. From fluorescence microscopic observation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Stein) (Lindemann, 1924) DINO NOC 1 4.00 Kempton et al, 2002;Saburova et al, 2012;Merino-Virgilio et al, 2014 Jiménez andGualancañay, 2006;Torres, 2011 Levanderina fissa (Levander) (Moestrup et al, Thangaraja et al, 2007;Wang et al, 2008;Ibrahem and Al-Shawi, 2015;Razali et al, 2015Torres, 2000, 2016Coello, 2003; Prorocentrum gracile (Schütt, 1895) DINO NOC 2 Gul and Saifullah, 2011;Muciño-Márquez et al, 2015;Anderson et al, 2017 Jiménez andIntriago, 2001; Tripos furca (Ehrenberg) (Gómez, 2013) DINO NOC 2 3 Edwards et al, 2006;Ibrahem and Al-Shawi, 2015;Razali et al, 2015;Yurimoto et al, 2015Torres, 2000To...…”
Section: Potentially Fish-killing and Bloom-forming Speciesmentioning
confidence: 99%
“…Stein) (Lindemann, 1924) DINO NOC 1 4.00 Kempton et al, 2002;Saburova et al, 2012;Merino-Virgilio et al, 2014 Jiménez andGualancañay, 2006;Torres, 2011 Levanderina fissa (Levander) (Moestrup et al, Thangaraja et al, 2007;Wang et al, 2008;Ibrahem and Al-Shawi, 2015;Razali et al, 2015Torres, 2000, 2016Coello, 2003; Prorocentrum gracile (Schütt, 1895) DINO NOC 2 Gul and Saifullah, 2011;Muciño-Márquez et al, 2015;Anderson et al, 2017 Jiménez andIntriago, 2001; Tripos furca (Ehrenberg) (Gómez, 2013) DINO NOC 2 3 Edwards et al, 2006;Ibrahem and Al-Shawi, 2015;Razali et al, 2015;Yurimoto et al, 2015Torres, 2000To...…”
Section: Potentially Fish-killing and Bloom-forming Speciesmentioning
confidence: 99%
“…If preferable prey organisms like diatoms occurred at such low cell densities, C. furca at high cell densities could be a possible alternative prey organism for D. lenticula. However, there was no evidence that D. lenticula digested C. furca in the study observation by Yurimoto et al (2015). This means that no microscopic organisms such as diatoms were present as prey for these two species.…”
Section: High Proportions Of Heterotrophic Cysts In Dinoflagellate Cymentioning
confidence: 59%
“…The following observation might be helpful for understanding abundant heterotrophic dinoflagellate cysts with less abundant prey organisms (e.g., diatoms) in the present study. Yurimoto et al (2015) reported interesting red-tide blooms along the coast of the Gulf of Thailand, consisting of two ecologically different dinoflagellate species-photo/mixotrophic Ceratium furca and heterotrophic Diplopsalis lenticula. C. furca is a non-cyst producing gonyaulacacean dinoflagellate that may form dense blooms in coastal waters in the southern part of the Andaman Sea (Karthik et al 2014) and in other areas.…”
Section: High Proportions Of Heterotrophic Cysts In Dinoflagellate Cymentioning
confidence: 99%
See 2 more Smart Citations